Exploring The Impact of Youtube Videos on The Speaking Proficiency of High School Students: Case Study at SMA Muhammadiyah Tenggarong - Meizyar Anandia Irawan; Ade Ismail Ramadhan Hamid (Departement of Mathematics Education, 2024)
This study examines the effect of YouTube video-based learning media on students at SMA Muhammadiyah Tenggarong. The purpose of this study is to determine whether there is a significant effect on improving students' English language skills. In this study, the author conducted quantitative research using the pre-experimental design method, which only involved one group of classes that were given a pre-test and post-test. The sample class consisted of twenty-one students. The class was taught to speak by using YouTube videos. As a result, YouTube video-based learning proved to be an effective pedagogical tool to improve students' speaking competence in social situations.